A psychometric analysis from the Item Response Theory: step-by-step modelling of a Loneliness Scale - Auné, Sofía Esmeralda (2020)
The Item Response Theory (IRT) is a set of psychometric models used in the development, assessment, improvement, and scoring of evaluating scales. This pedagogical article provides an initial overview of how to conduct, as well as interpret and present the results from, the application of IRT models suitable for ordered polytomous response options. The data used as an example for IRT modelling corresponds to the administration of the Buenos Aires Loneliness Scale (BALS), a new instrument for the assessment of loneliness self-perception. This data also corresponds to a nonprobabilistic and incidental sample of 509 participants residing in the Buenos Aires Metropolitan Area (53 % women). The objective of this article is to present an overview of the general steps and components needed to perform an IRT analysis, as a way to increase access to this powerful psychometric technique.